Relações entre família e escola: a parceria colaborativa no apoio à escolarização de alunos com autismo - Bittencourt, Daniele Francisca Campos Denardin de (2021)
Autism is described as a behavioral syndrome that includes impairments in social interaction and language/communication as well as repeated and stereotyped activities. In this way, the communication difficulties of the autistic student, who often cannot articulate what happens at school to his or her family or what happens at home to the school, leads to trouble exchanging information between the two contexts. Also, generalization is a frequent issue in educational settings. It is frequently a roadblock in these students' educational progress as skills gained in the classroom cannot be easily transferred from school to home or from home to school. As a result, several studies have investigated these interactions, pointing out the Collaborative Partnership (PC). This is characterized by the development of supportive relationships between school and home and the equivalence of shared interests. Thus, this study aims to provide a questionnaire to assess Collaborative Partnership indicators between family and school and examine the role of Collaborative Partnership indicators in these domains, particularly when it comes to the preparation and implementation of pedagogical interventions for students with Autism Spectrum Disorder. The study was performed in three public schools in Santa Maria, R.S. Eight teachers and five parents of autistic children took part in the study. A conceptual analysis was used to identify the Collaborative Partnership indicators. The ideas were then refined and synthesized using a descriptive organizational definition, resulting in developing a Theoretical Matrix of Collaborative Partnership Indicative Categories. The engagement and commitment indicators were mixed, and the communication indicator was omitted. The metrics were then turned into elements to be used in the development of an Interview Guide. The Questionnaire to Assess Indicators of Collaborative Partnership between Parents and Teachers was created afterwards. The parents addressed the Collaborative Partnership indicators identified by the teachers, and the teachers, the indicators listed by the parents. Then, the collected data were submitted to content analysis. The study generated six subcategories: commitment to content/lack of commitment to content, commitment to family and school relationships and external professionals/absence of commitment to family and school relationships and external professionals, school/social inclusion/lack of school/social inclusion, equity in decision-making/lack of equity in decision-making, and transparency in parent/teacher relationship and attention and care for the child/student/lack of transparency in parent/teacher relationship and attention and care for the child/student. In terms of the Collaborative Partnership and pedagogical interventions, it was possible to highlight the importance of taking into account the educational needs and desires of the child/student so that the pedagogical interventions can be modified, thus assisting teaching and encouraging collaborative activities that seek to improve child/student learning. In addition, regular interaction between parents and teachers is a deciding factor for a good Collaborative Partnership. For this reason, the study found that the use of social media, specifically through direct messaging groups, such as WhatsApp, has proven to be a significant ally to Collaborative Partnership.